Multiple Sulfatase Deficiency from an Ophthalmologist's Perspective-Case Report and Literature Review - Michael P. Schittkowski; Sabine Naxer; Mohamed Elabbasy; Leonie Herholz; Vivian Breitling; Alan Finglas; Jutta Gärtner; Lars Schlotawa (MDPI AG, 2023)
Multiple sulfatase deficiency (MSD) is an extremely rare autosomal recessively inherited disease with a prevalence of 1:500.000 caused by mutations on the sulfatase-modifying-Factor 1 gene (SUMF1). MSD is most specifically characterised by a combination of developmentally retarded psychomotoric functions, neurodegeneration that entails the loss of many already acquired abilities, and by ichthyosis. Other symptoms include those associated with mucopolysaccharidosis, i.e., facial dysmorphy, dwarfism, and hepatosplenomegaly. In 50-75% of all MSD-affected patients, functional or structural ocular damage is likely. MSD seldom affects the anterior segment of the eye. The main pathology these patients present is a highly conspicuous tapetoretinal degeneration, similar to severe Retinitis pigmentosa, that leads to blindness at an early age. An initially five-year-old boy with MSD, genetically verified at his first examination in our opthalmology department (SUMF1 mutations c.776A>T, p.Asn259Ile; c.797A>T, p.Pro266Leu; c.836A>T, p.Ala279Val), and a 4, 5 year regular follow-up are described. The patient had some visual potential ("tunnel view"), which deteriorated dramatically after his fifth birthday. We observed no evidence of worsening retinal involvement in this patient in spite of his progressively worsening clinical symptoms, extending to total blindness/no light perception. OCT revealed that the outer retinal layers containing photoreceptors were diseased; the ellipsoid zone was only partially discernible and the outer nuclear layer appeared to be thinned out. The inner nuclear layer, ganglion cell layer, and retinal nerve fibre layer were indistinguishable. These anomalies are indicative of a severe pathology within the retina's inner layers. Characteristic anomalies in the fundus should stimulate clinicians to suspect a case of MSD in their differential diagnosis, and thus to order thorough genetic and paediatric diagnostics.